The Effect of Demographic Factors Toward Willingness to Consume Porang and its Products as A Diet Menu Using Multinomial Logistic Regression Approach - Hidayati, Nurul; Triyono, Rudi; Wahyuni, Sri; Fadhilah, Rindi Anti Nur (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
The Indonesian authorities have echoed that Porang can be an opportunity for meals in the future. Currently, diverse applications are designed through the rules to help the improvement of Porang cultivation and industry. Although in truth, Indonesian human beings aren't acquainted with the life of Porang and its benefits. As a result, this study aimed to investigate the impact of demographic characteristics on willingness to consume Porang and its preparations as a diet menu. The study took place from July to October 2021, with 436 participants selected using a convenience sample procedure. The data was compiled from both primary and secondary sources. Primary data was collected by distributing online questionnaires via social media (Whatsapp and Instagram). While secondary information is gathered from journals, books, the internet, and other sources relevant to the research topic, primary data is gathered from primary sources. A multinomial logistic regression analysis evaluated the data, including five independent factors (monthly income, age, education, employment, and family category) and one dependent variable (willingness to use Porang/its product). According to the results, 49.3 percent of respondents said they would eat Porang on a diet menu. The respondents' occupation and degree of education influenced their propensity to take Porang as a diet menu (significance level 10 percent ). Programs could be organized according to the type of employment and level of education to undertake education and outreach to present Porang to the community.